MOLECULAR IDENTIFICATION AND PHYLOGENETIC ANALYSIS OF PLUM POWDER VIRUS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The damage caused by plum pox virus to agriculture in pome fruit plants is one of the pressing issues, with an annual cost of $600 million worldwide. As a result of molecular genetic comparison of the UZ1 Uzbekistan isolate with other strains in the world, similarities and differences were identified with isolates from other countries of the world. Phylogenetic tree analysis showed that the MT038048.1 UZ1 isolate, distributed in the Tashkent region, is located in a close phylogenetic subcluster with the KP198594.1 isolate isolated in Russia, and in the same phylogenetic cluster with the isolates isolated in Colombia and Slovakia.